Acting and knowledge of emergency rescue teams in dental trauma - Abu Hasna, Amjad [UNESP]; Ferrari, Carlos Henrique [UNESP]; Bittencourt, Tatiane Sampaio [UNESP]; Camargo, Carlos Henrique Ribeiro [UNESP]; Carvalho, Cláudio Antonio Talge [UNESP] (Editora Cubo, 2019)
Objective: Dental trauma is regularly frequent in patients assisted by rescue teams at sites of accidents and by emergency teams in hospitals. However, these professionals are given little or no information about taking care of the injured teeth and mouth. The aim of this study was to evaluate the level of knowledge of rescue and emergency teams’ professionals (physicians, Nurses, and Paramedics) concerning dental trauma first management. Material and methods: 196 professionals of rescue and emergency units had received a standard questionnaire of 5 questions concerning dental trauma first management and reserving avulsed dental tissue (a tooth or its fragment). Results: The results showed high level of attendance of dental trauma patients by paramedics, nurses, and physicians, with very low-level knowledge about dealing with such cases, and with moderate results about the best medium to preserve the avulsed tooth, and the actions taken during the rescue process. Conclusion: Our results show a high occurrence of cases of dental trauma attended by rescue and emergency medical teams, with a lack of knowledge, this suggests a need for more educational campaigns for these professionals with a long-term follow-up.
Atuação e conhecimento de equipes de resgate de emergência em casos de trauma dental
Keywords: Emergency rescue teams; Tooth Avulsion; Traumatic dental injury